Hadith #6683 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
The Prophet (ﷺ) used to invoke Allah in his prayer, “O Allah! Save `Aiyash bin Abi Rabi`a and Salama bin Hisham and Al-Walid bin Al-Walid; O Allah! Save the weak among the believers; O Allah! Be hard upon the tribe of Mudar and inflict years (of famine) upon them like the (famine) years of Joseph.”
Grade: Sahih

Hadith #6684 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “Whoever possesses the (following) three qualities will have the sweetness of faith (1): The one to whom Allah and His Apostle becomes dearer than anything else; (2) Who loves a person and he loves him only for Allah’s Sake; (3) who hates to revert to atheism (disbelief) as he hates to be thrown into the Fire.”
Grade: Sahih

Hadith #6685 - Sahih al-Bukhari - Qais bin Ubad (Sahih al-Bukhari)
I heard Sa`id bin Zaid saying, “I have seen myself tied and forced by `Umar to leave Islam (Before `Umar himself embraced Islam). And if the mountain of Uhud were to collapse for the evil which you people had done to `Uthman, then Uhud would have the right to do so.” (See Hadith No. 202, Vol. 5)
Grade: Sahih

Hadith #6686 - Sahih al-Bukhari - Khabbab ibn al-Aratt (Sahih al-Bukhari)
We complained to Allah’s Messenger (ﷺ) (about our state) while he was leaning against his sheet cloak in the shade of the Ka`ba. We said, “Will you ask Allah to help us? Will you invoke Allah for us?” He said, “Among those who were before you a (believer) used to be seized and, a pit used to be dug for him and then he used to be placed in it. Then a saw used to be brought and put on his head which would be split into two halves. His flesh might be combed with iron combs and removed fro
Grade: Sahih

Hadith #6687 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
While we were in the mosque, Allah’s Messenger (ﷺ) came out to us and said, “Let us proceed to the Jews.” So we went along with him till we reached Bait-al-Midras (a place where the Torah used to be recited and all the Jews of the town used to gather). The Prophet (ﷺ) stood up and addressed them, “O Assembly of Jews! Embrace Islam and you will be safe!” The Jews replied, “O Aba-l-Qasim! You have conveyed Allah’s message to us.” The Prophet (ﷺ) said, “That is what I want (
Grade: Sahih

Hadith #6688 - Sahih al-Bukhari - Khansa bint Khudham al-Ansariyya (Sahih al-Bukhari)
That her father gave her in marriage when she was a matron and she disliked that marriage. So she came and (complained) to the Prophets and he declared that marriage invalid. (See Hadith No. 69, Vol. 7)
Grade: Sahih

Hadith #6689 - Sahih al-Bukhari - 'Aisha and 'Abdullah bin 'Abbas (Sahih al-Bukhari)
I asked the Prophet, “O Allah’s Messenger (ﷺ)! Should the women be asked for their consent to their marriage?” He said, “Yes.” I said, “A virgin, if asked, feels shy and keeps quiet.” He said, “Her silence means her consent.”
Grade: Sahih

Hadith #6690 - Sahih al-Bukhari - Jabir ibn 'Abdullah (Sahih al-Bukhari)
A man from the Ansar made his slave, a Mudabbar. And apart from that slave he did not have any other property. This news reached Allah’s Messenger (ﷺ) and he said, “Who will buy that slave from me?” So Nu’aim bin An-Nahham bought him for 800 Dirham. Jabir added: It was a coptic (Egyptian) slave who died that year.
Grade: Sahih

Hadith #6691 - Sahih al-Bukhari - ibn Abbas (Sahih al-Bukhari)
Regarding the Qur’anic Verse: ‘O you who believe! You are forbidden to inherit women against their will.’ (4.19) The custom (in the Pre-lslamic Period) was that if a man died, his relatives used to have the right to inherit his wife, and if one of them wished, he could marry her, or they could marry her to somebody else, or prevent her from marrying if they wished, for they had more right to dispose of her than her own relatives. Therefore this Verse was revealed concerning this matter.
Grade: Sahih

Hadith #6692 - Sahih al-Bukhari - And Safiyya bint 'Ubaid (Sahih al-Bukhari)
“A governmental male-slave tried to seduce a slave-girl from the Khumus of the war booty till he deflowered her by force against her will; therefore ‘Umar flogged him according to the law, and exiled him, but he did not flog the female slave because the male-slave had committed illegal sexual intercourse by force, against her will.” Az-Zuhri said regarding a virgin slave-girl raped by a free man: The judge has to fine the adulterer as much money as is equal to the price of the female slave
Grade: Sahih

Hadith #6693 - Sahih al-Bukhari - Abu Hurairah (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “(The Prophet) Abraham migrated with his wife Sarah till he reached a town where there was a king or a tyrant who sent a message, to Abraham, ordering him to send Sarah to him. So when Abraham had sent Sarah, the tyrant got up, intending to do evil with her, but she got up and performed ablution and prayed and said, ‘O Allah ! If I have believed in You and in Your Apostle, then do not empower this oppressor over me.’ So he (the king) had an epileptic fit and
Grade: Sahih

Hadith #6694 - Sahih al-Bukhari - ibn Umar (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “A Muslim is a brother of another Muslim. So he should neither oppress him nor hand him over to an oppressor. And whoever fulfilled the needs of his brother, Allah will fulfill his needs.”
Grade: Sahih

Hadith #6695 - Sahih al-Bukhari - Anas ibn Malik (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “Help your brother whether he is an oppressor or an oppressed,” A man said, “O Allah’s Messenger (ﷺ)! I will help him if he is oppressed, but if he is an oppressor, how shall I help him?” The Prophet (ﷺ) said, “By preventing him from oppressing (others), for that is how to help him.”
Grade: Sahih